2012
DOI: 10.1002/jcp.22942
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐derived neurotrophic factor induces migration of endothelial cells through a TrkB–ERK–integrin αVβ3–FAK cascade

Abstract: Brain-derived neurotrophic factor (BDNF) promotes the regeneration of periodontal tissue. Since angiogenesis is important for tissue regeneration, investigating effect of BDNF on endothelial cell function may help to reveal its mechanism, whereby, BDNF promotes periodontal tissue regeneration. In this study, we examined the influence of BDNF on migration in human microvascular endothelial cells (HMVECs), focusing on the effects on extracellular signal-regulated kinase (ERK), integrin α(V)β(3), and focal adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 65 publications
2
64
0
Order By: Relevance
“…If such effects also occur in pulmonary vascular smooth muscle, this could regulate vascular remodeling and potentiate the effects of hypoxia on this process. Here, it is important to note a single previous finding that BDNF enhances migration of non-pulmonary endothelial cells [47]. Again, these alternate scenarios remain to be examined.…”
Section: Discussionmentioning
confidence: 93%
“…If such effects also occur in pulmonary vascular smooth muscle, this could regulate vascular remodeling and potentiate the effects of hypoxia on this process. Here, it is important to note a single previous finding that BDNF enhances migration of non-pulmonary endothelial cells [47]. Again, these alternate scenarios remain to be examined.…”
Section: Discussionmentioning
confidence: 93%
“…Several neurotrophic factors have been reported to stimulate angiogenic responses in vascular endothelial cells (42)(43)(44)(45). For example, brain-derived neurotrophic factor induces the survival and migration of endothelial cells and stimulates angiogenesis (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…BDNF activates Cdc42 (Sieg et al, 2000;Yuan et al, 2003;Myers et al, 2012), a member of the Rho family of small GTPases, which further activates myosin-II via MRCK (Gomes et al, 2005;Wilkinson et al, 2005), promotes F-actin polymerization by the N-WASP-Arp2/3 pathway (Carlier et al, 1999), and enhances point-contacts dynamics (Myers and Gomez, 2011;Matsuda et al, 2012;Myers et al, 2012), all of which can enhance the contractile activity of the cell. We found that when BDNF was applied together with the Cdc42 inhibitor ML141 (10-20 µM), the enhancement of force generation induced by BDNF was markedly reduced (Fig.…”
Section: Bdnf and Slit2 Regulate Traction Force And Guide Neuron Migrmentioning
confidence: 99%
“…For example, as an integrator and biosensor localized in adhesion sites (Mitra et al, 2005), FAK mediates the modulation of Cdc42 by extracellular guidance cues (Matsuda et al, 2012;Myers et al, 2012) and regulates cytoskeletal fluidity, GTPase activity, membrane composition, and the dynamics of focal adhesion, actin, and MTs (Mitra et al, 2005). Adhesion formation and disassembly drives the migration cycle by activating Rho GTPases, which in turn regulate actin polymerization and myosin-II activity, and therefore adhesion dynamics .…”
Section: The Role Of Substrate Adhesion In Migration and Force Generamentioning
confidence: 99%